Tangoing economics in a virtual classroom: recommendations for large classes instructors. (3rd April 2023) - Shostya, Anna
The COVID-19 pandemic has brought about dramatic changes to the classroom and has forced teachers on all levels and of all subjects to critically re-evaluate pedagogical strategies. Such transformative changes have created new opportunities and posed new challenges to college instructors, especially those who teach large lecture hall classes. This article provides practical guidance and useful instructional recommendations on how to create a highly collaborative experience for first-time learners of economics in a virtual classroom. Using the experience of teaching principles of microeconomics and macroeconomics to large lecture hall classes of mostly first-year college students, the author provides valuable insights on how to connect to a larger number of students, motivate them to 'do' economics, and stimulate their critical thinking and quantitative reasoning.